Oil film behaviour in hydrodynamic lubrication of journal bearing / Mohamad Ali Ahmad - Ahmad, Mohamad Ali (Institute of Graduate Studies, UiTM, 2015)
This thesis presents an integrated investigation of various aspects of hydrodynamic lubrication in a journal bearing. Hydrodynamic journal bearings are critical power transmission components used to carry high loads in different machines applications. In machine design, it is essential to know the true or expected operating conditions of the bearings. These operating conditions can be explored in laboratory using a specific test rig. In the present study, the hydrodynamics lubrication behaviour in a journal bearing has been investigated. The work described is based on the direct measurement of temperature, pressure, frictional force and ultrasonic reflection coefficients from a fluid interface using longitudinal and shear transducers. Measurement of temperature profile in hydrodynamic lubrication journal bearing has been investigated for different conditions later compared to predicted values from effective temperatures. In this study effective temperatures were calculated by two different methods using (1) Raimondi and Boyd charts and (2) inlet and outlet temperature values. From the results obtained, it was found that speed, load, oil inlet supply pressure and oil groove locations have affected the temperature profiles to some extent…